Estudos químicos e microbiológicos de microrganismos associados à esponja marinha Dragmacidon reticulatum, objetivando o isolamento de metabólitos secundários bioativos - Mizuno, Carolina Megumi (2010)
Fungi are known as one of the most promising sources of unprecedent bioactive compounds, however, marine derived fungi are still very poorly studied. These microorganisms present high percentages of active metabolites and they are commonly isolated from marine invertebrates. At this study, the associated microbiota of the marine sponge Dragmacidon reticulatum was investigated in order to know the microbial diversity and explore the biotechnological potential of those strains for the production of bioactive secondary metabolites. Fragments from D. reticulatum were incubated on Petri dishes with different growth media. Forty five strains were isolated, although only 40 presented satisfactory growth for the preservation and production of extracts. From these, 32 strains were analysed for their genetic polymorphism through the ARDRA method that showed 24 different ribotypes. Extracts produced from the growing media of the 40 strains were evaluated for their cytotoxic and/or antimicrobial activity. From those, 22 presented biological activities in at least one of the bioassays, and had their chemical profiles evaluated in HPLC-UV-MS. Considering only the different ribotypes, 20 strains were selected by the biological activity of their extracts and were submitted to molecular identification. These isolates were attributed to the Aspergillus, Penicillium, Cladosporium, Myrmecridium, Microphaeropsis, Sporidesmium and Westerdykella genera. One strain was identified as actinobacteria from the Streptomyces sp. genus, and had its extract investigated, because the marine derived actinobacteria are also potential sources of bioactive compounds. The isolation of the unprecedented compounds _,_-dehydrocurvularin, the I-6, O-2 and JKL-4, produced by the fungus Penicillium decaturense, demonstrated the effectiveness of the screening procedures used in strain selection as producers of metabolites of biotechnical interest, and the need of more studies with this strain and the other strains selected in this study (Streptomyces sp., Westerdykella sp. and Sporidesmium sp.). The results confirmed the biotechnological potential presented by marine derived fungi.